Mending Broken Soldiers : the Union and Confederate Programs to Supply Artificial Limbs. - Hasegawa, Guy R. (Southern Illinois University Press, 2012)
The four years of the Civil War saw bloodshed on a scale unprecedented in the history of the United States. Thousands of soldiers and sailors from both sides who survived the horrors of the war faced hardship for the rest of their lives as amputees. Now Guy R. Hasegawa presents the first volume to explore the wartime provisions made for amputees in need of artificial limbs-programs that, while they revealed stark differences between the resources and capabilities of the North and the South, were the forebears of modern government efforts to assist in the rehabilitation of wounde.